Implementation of Customer Relationship Management (CRM) to Automate Logging Track Record Students And Alumni - Robby Yuli Endra; Fenti Ariani; Septiany Dian Puspita; Ade Kurniawan (Bandar Lampung University (UBL), 2014)
Biro Pembinaan Kemahasiswaan dan Hubungan Alumni (BPKHA) Bandar Lampung University has one of the tasks for the alumnus record, but the way that used by BPKHA UBL still manually so that the alumnus data that are collected, it has not been gathered maximally. Therefore, the researchers examined the problem by tracking the footsteps of alumni studies or surveys of graduates have been made one of college accreditation requirements by using Customer Relationship Management (CRM ), because such methods focus on how to attract the alumnus so that they always fill up the alumnus form and register themselves in detail . Tracer Study becomes increasingly important role as it can provide important information for the development of higher education . Additionally tracer study acts as a tool to evaluate the relevance between higher education and the world of work, it can provide useful input for lecturer and administrator to improved performance, as well as give feedback to parents in monitoring their children's education ( Schomburg, 2006 ). From the analysis and the design that have been successfully fabricated, The Software of Information System of Students and Alumnus Record Traces Based Customer Relationship Management (CRM) for Automation. Data Collection, with the stages of planning , analysis, design, implementation and testing. The system is constructed to provide information to the University and alumnus as well as students either acquire phase, enhance, and retain with different features are tailored to the results of the analysis.